Children and television : a global perspective - Lemish, Dafna, 1951- (Malden, MA : Blackwell Pub., 2007)
"This book offers an overview on children and television from the accumulated global literature in this field of the past 50 years, combining both the American tradition, influenced heavily by developmental psychological studies, as well as the European tradition, characterized by more sociological and cultural studies perspectives to the field. Similarly, it draws together a methodological diversity from both the quantitative-experimental and survey research, together with the qualitative-ethnographic and interview research of children and television."--Jacket.
5. Television and learning -- Television and school -- two educational systems -- Viewing television and performance in school -- Television and language acquisition -- Acquisition of native language -- Acquisition of second language -- The audio-visual language and cognitive skills -- The development of special viewing skills -- Learning from educational television -- The development of educational television -- Theoretical models for evaluating learning from educational television -- Children's Television Workshop (CTW) (Sesame Workshop, SW) -- The Teletubbies -- Concluding remarks -- Notes -- 6. Implications for education and policy -- Media literacy -- The central debates in media literacy -- Media literacy around the world -- Practical aspects of media literacy -- The curriculum -- Teaching -- Assessment -- Evaluating media literacy curricula -- Policy of broadcasting for children -- Central content-related policy issues -- Policy regarding television violence -- Policy regarding television advertising -- Policy regarding sponsorship of children's programs -- Convention on television broadcasting for children and youth -- Notes -- 7. Conclusion : growing up in a global screen culture -- Globalized screen culture -- The changing of childhood -- A research agenda -- Notes -- Recommended sources for additional readings -- References -- Index.
Includes bibliographical references (p. [222]-245) and index.
Keywords: Television and children; Television in education; Television broadcasting -- Social aspects